IMPORTANCE OF LICORICE PLANT IN HUMAN LIFE - Mamasodiqov Sodiqjon Mahmudjon Ugli; Qurbonova Nafisa Avaz qizi; Kholbozorova Madina Ravshan qizi (Galaxy International Interdisciplinary Research Journal, 2022)
Currently, the demand for medicinal and useful plants for the national economy is increasing. For this reason, the Ministry of Innovative Development of the Republic of Uzbekistan, in the formation of the state scientific programs of applied and innovative research for 2019-2021, organized competitions for projects on the development of modern technologies for the cultivation of licorice and other medicinal plants, and as a result of the conducted research, the plant useful aspects are being studied.